2007
DOI: 10.1002/jcop.20186
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an integrated, trauma‐informed approach to treating women with co‐occurring disorders and histories of trauma: The Los Angeles site experience

Abstract: Ⅲ Effectiveness of an integrated trauma-informed approach to treating women with co-occurring disorders and histories of trauma was evaluated. Baseline and 12-month assessments were completed by 136 interventionand 177 comparison-group women. The intervention group received

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 22 publications
3
51
1
1
Order By: Relevance
“…The WCDVS found that across treatment sites, IT reduced trauma at the 12-month follow-up but not SUD symptoms (Morrissey et al, 2005). To note, IT was associated with SUD improvement at follow-up by two individual WCDVS sites (Amaro et al, 2007;Gatz et al, 2007). IT also generally produced favorable outcomes in studies receiving a weak QAT rating.…”
Section: Study Outcomesmentioning
confidence: 86%
See 1 more Smart Citation
“…The WCDVS found that across treatment sites, IT reduced trauma at the 12-month follow-up but not SUD symptoms (Morrissey et al, 2005). To note, IT was associated with SUD improvement at follow-up by two individual WCDVS sites (Amaro et al, 2007;Gatz et al, 2007). IT also generally produced favorable outcomes in studies receiving a weak QAT rating.…”
Section: Study Outcomesmentioning
confidence: 86%
“…However, winsorization of the large sample size (for the meta-analysis) pushed the small WCDVS PTSD effect to nonsignificance. Also to be noted, traumainformed care was associated with greater SUD improvement in two individual sites of the WCDVS at the 12-month follow-up (Amaro et al, 2007;Gatz et al, 2007). Fig.…”
Section: Are It Programs Superior To Non-it Programs?mentioning
confidence: 87%
“…Our findings may have particular relevance for engaging women in services that historically have been perceived as male-oriented. Recent studies that have attempted to provide additional services to women to address gender-specific needs have evidenced better outcomes than traditional treatment (e.g., Morissey et al, 2004;Gatz et al, 2007). However, more research is needed to address complex issues such as the degree to which treatments need to be gender-specific in content versus merely single-gender in format (e.g., women-only treatment).…”
Section: Discussionmentioning
confidence: 99%
“…These groups focused on helping clients understand the co-occurrence of substance abuse and trauma, and the impact of both on their daily functioning. Studies of this intervention have had promising results with regard to reductions of trauma symptoms and substance use (e.g., Desai, Harpaz-Rotem, Najavits, & Rosenheck, 2008;Gatz et al, 2007). While Seeking Safety is appropriate for use by men and women, fewer studies have been conducted on men's outcomes; however, a summary of several pilot studies found that men also find the intervention helpful (Najavits et al, 2009).…”
Section: Interventionsmentioning
confidence: 94%